Powering West Africa: modelling sustainable long-term electricity planning. (25th March 2019) - Seck, Mamadou; Toba, Ange-Lionel
This paper presents a tree-like exploration method to analyse strategies for the development of grids of the future in West Africa. The approach helps generate plausible future grids, based on demand requirements and resource availability, by either building power plants or transmission lines. These grids are generated via a modelling framework, Spark!, which captures key components of the power system, as well as relationships between them. Spark! analyses financial, environmental and reliability performances, and also addresses concerns caused by high renewable penetration in large-scale power grids. Contrary to other models used to address long-term planning in African countries, Spark! performs long-term planning of energy resource use to satisfy the demands, but also simulates grid operations in real-time. It enables decision makers to examine long-term effects of decisions made, but also observe how the system responds to these decisions.